One-Size-Fits All: A Scalable Solution to Formal Telemedicine Provider Training to Support the COVID-19 Pandemic Response - Schinasi, Dana A.; An-Grogan, Yuemi; Stephen, Rebecca; Shimek, Aric; Furney, Marisa; Bohling, M. Katie (Frontiers in Pediatrics, 2021)
Introduction: Formalized training in telemedicine addresses barriers to provider adoption and engagement and assures a level of competence for independent practice. We previously developed a blended-model training program, customizable according to role and specialty; this method of training was not feasible in the pandemic response. We describe the development and implementation of a multi- and interdisciplinary telemedicine provider training program enabling the rapid scaling of telemedicine at our institution. Methods: An existing curriculum was pared down to a 1-hour session delivered synchronously, covering the foundational components of telemedicine practice. Supplemental materials were available for asynchronous learning via the hospital intranet. Completion of training was required of all clinicians who practice telemedicine. Results: We conducted 35 sessions for 1,070 providers over 12 weeks. Attendees included clinicians across numerous roles and specialties. Additional resources were created and available through the Telemedicine Virtual Handbook and housed in specific toolkits. Discussion: Telemedicine training is necessary for consistent, competent practice of telemedicine in pediatrics. We describe a training process that can be easily replicated and rapidly deployed to providers of telemedicine across roles and disciplines. Combining a mandatory and brief synchronous provider training session with a repository of online resources creates a foundation for consistent practice, while allowing for more individualized resources accessible on demand. Standardized telemedicine training followed by mechanisms for ongoing professional practice evaluation allow institutions to ensure consistent and competent practice of telemedicine. Further study is needed to determine the best modality for training, and optimal assessment tools according to professional role.